Short stays, high needs: gender disparities in Czech forensic psychiatric inpatient care - Páv, Marek; Pekara, Jaroslav; Valeš, Jáchym; Závora, Jiří; Korený, Dominik; Zahrádka-Köhlerová, Michaela; Anders, Martin; Kitzlerová, Eva (Frontiers in Psychiatry, 2025)
IntroductionLimited research has explored the sociodemographic profiles, institutional behaviours, and treatment needs of women receiving forensic psychiatric care, particularly in Eastern Europe. Existing evidence suggests that women differ from men in several clinically significant ways that impact service delivery, treatment strategies, and overall care.MethodsA cross-sectional design was employed involving 85 women and 753 men across 14 forensic psychiatric facilities in the Czech Republic. Data were collected at two-time points, six months apart, using the Health of the Nation Outcome Scale-Secure (HoNOS-secure) and the Modified Overt Aggression Scale (MOAS). Gender differences in psychiatric diagnoses, length of stay (LoS), aggression, and unmet needs were statistically analysed.ResultsThe mean age of women was 45.08 years, compared to 41.43 years for men. Women had a significantly shorter average LoS (893.27 days; SD 116–3935) than men (1358.36 days; SD 28–15311). Women were more often diagnosed with psychotic and substance use disorders, had higher rates of violent index offences, and were 2.33 times more likely to receive antipsychotic medications. Although women initially demonstrated higher MOAS scores, they showed significant improvement over time. Both genders exhibited reduced security needs at follow-up. Nonetheless, high levels of unmet needs remained, particularly among women.ConclusionsThe findings emphasise the importance of gender-responsive approaches in forensic psychiatric care. Establishing specialised forensic units for women is crucial to addressing their distinct clinical and psychosocial needs, enhancing treatment outcomes, and reducing recidivism. This study identifies critical service delivery gaps and reinforces the need to develop targeted interventions tailored to women in forensic settings.